2012
DOI: 10.26719/2012.18.4.346
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and pattern of menstrual disorders among Lebanese nursing students

Abstract: Menstrual disorders frequently affect the quality of life of adolescents and young adult women and can be indicators of serious underlying problems. The objective of this study was to determine the prevalence and pattern of menstrual symptoms among nursing students in Beirut, Lebanon. Of 352 students completing a written questionnaire, the most common menstrual disorders were irregular frequency of menstruation (80.7%), premenstrual syndrome (54.0%), irregular duration of menstruation (43.8%), dysmenorrhoea (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
105
8
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(135 citation statements)
references
References 35 publications
12
105
8
10
Order By: Relevance
“…This was lower than the previous studies conducted in Saudi (92%) [46] Nigeria (76%) [47], but higher than the studies carried out in Lebanon (63.1%) [48] Ethiopia (72%) [8]. We found that the prevalence of dysmenorrhoea (OR: 3.048) and leucorrhoea (OR: 2.889) were associated with abnormal menstrual cycle.…”
Section: Menstrual Pattern and Disorderscontrasting
confidence: 56%
“…This was lower than the previous studies conducted in Saudi (92%) [46] Nigeria (76%) [47], but higher than the studies carried out in Lebanon (63.1%) [48] Ethiopia (72%) [8]. We found that the prevalence of dysmenorrhoea (OR: 3.048) and leucorrhoea (OR: 2.889) were associated with abnormal menstrual cycle.…”
Section: Menstrual Pattern and Disorderscontrasting
confidence: 56%
“…15 Karout et al in Saudi Arab, Jan et al in Pakistan, Oche et al in Nigeria, Lawan et al in Nigeria, Poureslami et al in Tehran highlighted mother as main source of information and teacher playing a minor role. [16][17][18][19][20] However, few studies quoted teachers and friends as the main source of information. Kumar et al in urban area of Garhwal, Uttarakhand reported friends were the first informant in case of 196 (46.75%) girls and it was followed by mother (26.8%).…”
Section: Discussionmentioning
confidence: 99%
“…With onset of menstruation a girl becomes aware of her emerging identity as a female capable to reproduce. Her understanding and acceptance of her new identity will be greatly influenced by the feedback she receives from peers, educators and most importantly her parents (6,7). Menstruation occurs periodically throughout the child bearing years, except during pregnancy and lactation.…”
Section: Imentioning
confidence: 99%